A review of surface modification of a novel low modulus β-type titanium alloy for biomedical applications. (1st January 2014) - Niinomi, Mitsuo; Nakai, Masaaki; Hieda, Junko; Cho, Ken; Kasuga, Toshihiro; Hattori, Tomokazu; Goto, Takashi; Hanawa, Takao
Ti-29Nb-13Ta-4.6Zr (TNTZ) is a novel β-type titanium alloy that has great potential use in biomedical implants because of its relatively low Young's modulus (around 60 GPa), which minimise bone atrophy due to stress shielding. However, the biocompatibility and bio-functionality of TNTZ is poor. Therefore, a bioactive ceramic surface modification or soft-tissue-compatible polymer surface modification is advantageous for enhancing the biological properties of TNTZ. The bio-functionality of TNTZ itself, and that modified with a coating hydroxyapatite (HAp) using alkali treatment, electrochemical treatment, and dip-coating treatment with calcium phosphate glass ceramic or metal organic chemical vapour deposition (MOCVD) is assessed. In addition, modification of TNTZ with soft-tissue-compatible segmented polyurethane (SPU) using different silane coupling agents is described. The bonding strength of the bioactive ceramic and soft-tissue compatible polymer with the TNTZ is assessed with respect to variations in surface roughness.